2014
DOI: 10.1002/2013jb010186
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating seasonal loading models and their impact on global and regional reference frame alignment

Abstract: Seasonal variations are observed in GPS time series, but are not included in the International Terrestrial Reference Frame (ITRF) models. Unmodeled seasonal variations at sites used for reference frame alignment are aliased into the reference frame parameters and bias all coordinates in the transformed solution. We augment ITRF2008 with seasonal loading models based either on Gravity Recovery and Climate Experiment (GRACE) measurements or a suite of models for atmospheric pressure, continental hydrology, and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 44 publications
2
33
0
1
Order By: Relevance
“…Always some aliasing of (small) position offsets in the Helmert transformations will take place during the (numerical) matching of the predicted (IGS08) and computed GPS position of each included IGS08 reference station. This is somewhat similar to the more extreme case of exclusively using a regional IGS sub-network where seasonal signals are reduced as these are aliased in the reference frame transformation parameters as has been observed by several other studies (Freymueller 2009;Legrand et al 2012;Zou et al 2014). In our case this aliasing seems to be more of a (seasonal) position misfit balancing nature that depends on the size and geometry of the chosen global IGS08 sub-network.…”
Section: Weekly Combinations In Igs08supporting
confidence: 81%
See 1 more Smart Citation
“…Always some aliasing of (small) position offsets in the Helmert transformations will take place during the (numerical) matching of the predicted (IGS08) and computed GPS position of each included IGS08 reference station. This is somewhat similar to the more extreme case of exclusively using a regional IGS sub-network where seasonal signals are reduced as these are aliased in the reference frame transformation parameters as has been observed by several other studies (Freymueller 2009;Legrand et al 2012;Zou et al 2014). In our case this aliasing seems to be more of a (seasonal) position misfit balancing nature that depends on the size and geometry of the chosen global IGS08 sub-network.…”
Section: Weekly Combinations In Igs08supporting
confidence: 81%
“…The shorter 2009-2011 data period is more susceptible to this especially as it continues beyond the latest data inputs into ITRF08/IGS08. However, mainly a larger spread/variation in the velocity differences in each direction is observed here (Table K) The seasonal variations remain similar using either method for both data periods ( Legrand et al 2012;Zou et al 2014). …”
Section: Weekly Combinations In Igs08mentioning
confidence: 53%
“…However, it has been reported that annual signals in GPS observations only decrease slightly when applying GRACE‐modeled CVD corrections to GPS time series at stations spread worldwide [ Tregoning et al , ; Horwath et al , ; Tesmer et al , ; Zou et al , ]. Errors or limitations in both the GPS and GRACE systems may result in low root‐mean‐square (RMS) reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Nontidal ocean mass loads are derived from the 3-hourly ocean bottom pressure on a regular 1.0°× 1.0°global grid from the MPIOM ocean model (van Dam et al, 2012). Notably, the environment loads vary among different data centers (Jiang et al, 2013;Zou et al, 2014). Since our main purpose is to study the impact of bedrock thermal expansion on the GPS height time series, only the Deutsche GeoForschungsZentrum (GFZ) products are selected here for reference (Dill & Dobslaw, 2013).…”
Section: Geophysical Research Lettersmentioning
confidence: 99%